GÖRME ENGELLİ SPORCULARDA PERFORMANSI ETKİLEYEN PSİKOLOJİK FAKTÖRLER: NİTEL BİR ÇALIŞMA - ÇERİ, HASAN (Fırat Üniveristesi, 2024)
[Abstract Not Available]
Psychological factors affecting performance in visually disabled athletes: A qualitative study
Keywords: Spor